Packaging waste in Poland - current status and perspective = Gospodarowanie odpadami opakowaniowymi w Polsce - stan obecny i perspektywa - Zarębska, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The article presents the results of research, whose aim was to answer the question of how changing consumer trends affect the implementation of the requirements of the Waste Act and the Act on packaging and packaging waste. The new EU directive enacted in July 2014 tightens the requirements towards waste management in the EU, and this is especially evident in the increased levels of recovery and recycling of packaging waste.
Keywords: odpady; odzysk opakowań; dyrektywa COM(2014) 397 final; świadomość ekologiczna; wastes; medicines; packaging recovery; direktive COM(2014) 397 final; environmental awareness